Latilactobacillus sakei strains protect crucian carp against Aeromonas hydrophila–induced intestinal injury in an oral challenge model - Zhao, Yan; Li, Ruizhe; Zhu, Ting; Hu, Huanhuan; An, Guanghui; Ren, Zhangheng; Cui, Jie; Jiang, Jinchi (Frontiers in Nutrition, 2026)
In aquaculture, the overuse of antibiotic could lead to antimicrobial resistance and destabilize host–microbiota homeostasis. Latilactobacillus sakei, belonging to the genus Latilactobacillus, was included in the list of bacteria that could be used in food in China in 2014. Increasing evidence demonstrated that its antagonistic capacity against a broad spectrum of pathogenic bacteria, indicating its promising potential for application in aquaculture. In this study, the protective effect of three L. sakei (JO12, JO26, JO35), isolated from the intestine of fish and shrimp, on mucosal injury caused by Aeromonas hydrophila in crucian carp under an oral challenge model was investigated. The result showed that compared with LGG, all three L. sakei strains alleviated A. hydrophila induced intestinal barrier damage and inflammation (downregulated intestinal TNF-α/IL-1β, upregulated IL-10, and reduced MyD88) in crucian carp. L. sakei JO35 delivered the greatest improvement in growth and feed efficiency. Compared with the model group, L. sakei JO26 and JO35 significantly decreased the levels of serum acid phosphatase (ACP) and increased intestinal lysozyme, whereas L. sakei JO12 lowerd serum ACP but exacerbated the elevation of intestinal AKP. Microbiome and transcriptome analysis revealed that the protective effect of L. sakei may be associated with the strain’s intestinal colonization capacity and its regulation of phagolysosomal competence (lysosome/phagosome, LAMP) and IgA barrier via pIgR (prominent with JO35).